2021
DOI: 10.3390/membranes11020119
|View full text |Cite
|
Sign up to set email alerts
|

Desalination of Municipal Wastewater Using Forward Osmosis

Abstract: Membrane technology has gained much ground in water and wastewater treatment over the past couple of decades. This is timely, as the world explores smart, eco-friendly, and cheap water and wastewater treatment technologies in its quest to make potable water and sanitation commonplace in all parts of the world. Against this background, this study investigated forward osmosis (FO) in the removal of salts (chlorides, sulphates, and carbonates) and organics (chemical oxygen demand (COD), turbidity, total suspended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 46 publications
(54 reference statements)
0
22
0
Order By: Relevance
“…Ezugbe et al [ 22 ] researched the desalination of municipal wastewater using FO. They used a similar CTA FO membrane operated in the FO mode to desalinate the wastewater.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ezugbe et al [ 22 ] researched the desalination of municipal wastewater using FO. They used a similar CTA FO membrane operated in the FO mode to desalinate the wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…They used a similar CTA FO membrane operated in the FO mode to desalinate the wastewater. Their results showed that the FO membrane reduced COD by approximately 60% [ 22 ]. However, the efficiency achieved in this project for COD removal using the same FO membrane was 100%, mainly because the PSWW was pretreated with UF.…”
Section: Resultsmentioning
confidence: 99%
“…Forward Osmosis (FO) is a membrane technology of growing interest for resource recovery from municipal wastewater. The high contaminant rejection and lower fouling of the forward osmosis membrane compared to pressure-driven membrane processes such as reverse osmosis, nanofiltration, and ultrafiltration make it a promising alternative for pre-concentrating municipal wastewater [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. On the other hand, reverse osmosis technologies are now a fundamental part of the process of procurement of drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, membrane separation technology has received tremendous attention owing to its simple process, high separation efficiency, and environmental friendliness. 1,2 Pervaporation is a membrane separation process with a phase transition, 3,4 which can separate the components of a mixture based on the differences in dissolution and diffusion ability. During this process, those membranes with high selectivity enable efficient recovery of the target substances.…”
Section: Introductionmentioning
confidence: 99%